Urdu Qaida KG - The city school (Lahore, Pakistan The city school.)
The KG Urdu Qaida is designed to introduce young learners to the Urdu alphabet and basic phonics. It focuses on letter recognition, pronunciation, and simple word formation through engaging visuals and activities. The Qaida helps children develop reading and writing skills, fostering a strong foundation in Urdu language literacy. It is aimed at making the learning process fun and accessible for kindergarten students.
The KG Urdu Qaida is designed to introduce young learners to the Urdu alphabet and basic phonics. It focuses on letter recognition, pronunciation, and simple word formation through engaging visuals and activities. The Qaida helps children develop reading and writing skills, fostering a strong foundation in Urdu language literacy. It is aimed at making the learning process fun and accessible for kindergarten students.